2001
DOI: 10.1038/nn781
|View full text |Cite
|
Sign up to set email alerts
|

An auditory domain in primate prefrontal cortex

Abstract: Although neuroimaging studies confirm the frontal lobe's involvement in language processes and auditory working memory, the cellular and network basis of these functions is unclear. Physiological studies of the frontal lobe in non-human primates have focused on visual working memory and auditory spatial processing in dorsolateral prefrontal cortex (PFC), although the candidate PFC areas for non-spatial acoustic processing lie in the ventrolateral PFC (areas 12 and 45), which receives afferents from physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
261
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(287 citation statements)
references
References 15 publications
19
261
7
Order By: Relevance
“…This proposed role is consistent with previous hypotheses regarding this region's role in the processing of acoustically meaningful communication signals (Deacon 1992;Jü rgens 2002). Since communication is often multimodal (Hinde & Rowell 1962;Hauser et al 1993;Partan & Marler 1999) and since vPFC neurons respond to visual stimuli (Romanski & Goldman-Rakic 2002), an interesting question to consider is whether this circuit represents auditory as well as visual communication signals and represents this information in a modalityindependent format (Ghazanfar & Logothetis 2003).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This proposed role is consistent with previous hypotheses regarding this region's role in the processing of acoustically meaningful communication signals (Deacon 1992;Jü rgens 2002). Since communication is often multimodal (Hinde & Rowell 1962;Hauser et al 1993;Partan & Marler 1999) and since vPFC neurons respond to visual stimuli (Romanski & Goldman-Rakic 2002), an interesting question to consider is whether this circuit represents auditory as well as visual communication signals and represents this information in a modalityindependent format (Ghazanfar & Logothetis 2003).…”
Section: Resultssupporting
confidence: 89%
“…The vPFC was identified by its anatomical location and its neurophysiological properties. Anatomically, the vPFC is located anterior to the arcuate sulcus and area 8a, and it lies below the principal sulcus (Romanski & Goldman-Rakic 2002). The recording sites were similar to those reported in previous studies from our laboratory (Cohen et al 2004;.…”
Section: Methodssupporting
confidence: 84%
“…The observation that early peripheral visual representations are connected with caudal auditory cortex is consistent with a ''dorsal-pathway'' type function of these multisensory connections (Falchier et al 2002). Indeed, caudal auditory areas are considered to be part of a dorsal auditory stream, based on their connections with spatial domains of the frontal lobe and their role in sound spatial localization (Rauschecker 1998;Romanski, Bates, et al 1999;Romanski, Tian, et al 1999;Romanski and Goldman-Rakic 2002;Rauschecker and Tian 2004). Recent findings from fMRI connectivity analysis in humans showed that auditory cortex has a distinct relationship with the peripheral representation of visual field in the calcarine sulcus (Eckert et al 2008;Cate et al 2009).…”
Section: Visual Field Eccentricity and Multimodal Connectionsmentioning
confidence: 66%
“…Instead of low-level auditory features, these neurons seem to Single cell activity was usually recorded in BA 45A and BA 9/46v, both located rostrally to BA 8Av below the principal sulcus. Color-coded dots refer to the following studies: (Gifford et al, 2005), Romanski et al, 2005), (Cohen et al, 2007Russ et al, 2008a), (Romanski and Goldman-Rakic, 2002), (Cohen et al, 2006), (Lee et al, 2009;Russ et al, 2008b), (Sugihara et al, 2006), and (Gil-da-Costa et al, 2006) for activity in the vPM. Abbreviations: as arcuate sulcus, cs central sulcus, ipd inferior precentral dimple, ls lateral sulcus, ps principal sulcus, vpm ventral premotor area.…”
Section: Origins Of the Ifc Sensitivity To Vocal Intonationsmentioning
confidence: 99%